(3GdGMUGA GdeJbOe aj OYe GdbQGQ (B:s (3HGdJQcjRYdi efXeGJ GdGYeGd GdGfJGLjI (B/s - (3GdfYjej, eMeO YHO GdYGds ((3YeGf(B: s (3OGQ GdhQGb(B, s, 2007)
(3eaGgje YGeI aj GSGdjH hUjZ OYe GdbQGQ aj efXeGJ GdCYeGd, GdGMJeGdGJ aj OYe GdbQGQ, GdeJZjQGJ GdYThGFjI hGdJhRjYGJ GdGMJeGdjI, GNJHGQ GdaQVjGJ GdGMUGFjI, GSJNOGe JhRjY (B(T) (3aj GNJHGQ GdaQVjGJ, GdSdGSd GdRefjI aj OYe GdbQGQ, bjGS GdLhOI hGdSjWQI YdjgG, GdefgL GdGMUGFj hOhQg aj OYe GdbQGQs
(3HHdjhZQGajG(B: (3U(B.443-446 (3GdedGMb U(B.447s
Keywords: (3GOGQI GdGYeGds; (3GOGQI GdGfJGLs; (3GdGMUGAs